The impact of ethnic self-identity on post-migration social integration of young rural to urban migrants in China: An interpretative phenomenological analysis - Tianning Li (PLoS ONE, 2026)
Background Post-migration social integration is a pressing concern for young ethnic-minority migrants in urban China. This study examines how ethnic self-identity shapes this integration process from the migrant’s own lived perspectives. Using an interpretative phenomenological approach, we regard young migrants as subjects of meaning-making rather than objects to be measured. Ecological systems theory, social identity theory, and social cognitive models provide the analytical frameworks for understanding how ethnic identity is negotiated within destination-city contexts. Methods We conducted 30 semi-structured interviews with ethnic migrant youths from Miao, Tujia, and Zangzu (Tibetan) groups who had relocated to Wuhan, Hubei Province. Data were analyzed using Interpretative Phenomenological Analysis, with cross-case patterning organized through thematic procedures. Results Analysis identified five interconnected experiential dimensions of ethnic self-identity that influence social integration: ethnic self-categorization, ethnic versus local language proficiency, ethnic and cultural practices, perceived ethnicity- based discrimination and bicultural identity integration. Conclusion Ethnic self-identity functions as a two-sided mechanism: it simultaneously provides psychological protection against discrimination and sustains ethnic group cohesion, yet also creates social boundaries that complicate host-community integration. These findings highlight the need for policies and interventions that address both identity-based support and structural barriers to integration.